BUDGET TURBULENCE AND BUDGET DEVIATION: DO LOCAL GOVERNMENT HAVE THE ABILITY TO REDUCE THEM? - Herianti, Eva (Jurnal Tata Kelola & Akuntabilitas Keuangan Negara, 2019)
The purpose of this study is to examine and analyse the effect of local governments’ ability on the relationship between budget turbulence and budget deviation. The study sample uses the regional budget (APBD) report and realization of a number of districts/cities throughout Indonesia encompassing the 2014-2017 period, while the analysis covers the period from 2015-2017. This study uses the least square approach with EViews analysis tool version 10 to test the hypothesis. Result of the study shows that budget turbulence has a positive and significant effect on budget deviation. The result also shows that the capacity of local governments can reduce the influence of budget turbulence on the budget deviation. Sensitivity tests using proxies of local governments not sampled by the main test also show consistent results. Finally, sensitivity test by area category proves that for the three categories, mainly western, central, and eastern Indonesia, the results are consistent with the main test results. The contribution of this study to the policies of the local governments is aimed to enhance efficiency of spending and increase productive spending to support the priority of government programs and encourage efficient, innovative and sustainable financing while maintaining the investment climate. Through several of these alternatives, the local government can overcome the conditions of resource instability that can threaten the effectiveness of the implementation of various programs.